Norm Compliance and Lying Patterns: an Experimental Study Among Refugees and Non-refugees in Syria, Jordan, and Germany - Nora El-Bialy; Elisa Fraile Aranda; Andreas Nicklisch; Lamis Saleh; Stefan Voigt (University of Hamburg, Institute of Law and Economics (ILE), 2021)
We report the results of an experiment on norm violation, specifically lying, in a repeatedly played mind game with Syrian refugees in Jordan and in Germany. We compare their behavior with Jordanians, Germans, and Syrians who still live in Syria. The average number of lies is amazingly similar - and low - across all five samples. However, the lying patterns of Syrian refugees are very different from non-refugee participants in Germany, Jordan, and Syria itself. After having lied once, refugee participants resort to a "never return"- pattern significantly more often than the nonrefugee participants. A closer look at the socio-demographic characteristics of our Syrian refugee participants reveals that lying is associated with higher age and gender, while a longer stay in the host country is positively correlated with a lower likelihood of reporting extreme numbers of matches.
Keywords: C93; D01; O15; 330; Civil war; experimental economics; honesty; lying; psychological distress